MODEL SUPERVISI ARTISTIK - RELIGIOUS HUMANISTIC KEPALA MTS AL KAUTSAR SIDANG ISO MUKTI KEC. RAWAJITU UTARA, KAB. MESUJI (Pascasarjana IAIN Kudus, 2015)
Supervision Artistic religious-humanistic is the development of a model of artistic supervision, the deepening of the person’s religious values inspiringthis supervision model that implemented in performing his duties as a leader and supervisor in an agency or institution. Supervision artistic religioushumanistic is a model of supervision that develops relationships between superiors and subordinates well, placing the teachers and the staff are equal as human beings or God’s creatures and to drop barriers or differentiator like place in the job and other background as a form of implementation of thevalues of religiosity that there is in a person. The principal of MTs Al Kautsar North Rawajitu applied this supervision model. The religiosity values make the Principal as a humble and capable leader in social interaction, resilient and protecting as superiors, decisive and insightful or visionary future.